New Viscosity Correlation for Different Iraqi Oil Fields - Kaiser Abdulmajeed, Rwaida (Iraqi Journal of Chemical and Petroleum Engineering, 2014)
Viscosity is one of the most important governing parameters of the fluid flow, either in the porous media or in pipelines. So it is important to use an accurate method to calculate the oil viscosity at various operating conditions. In the literature, several empirical correlations have been proposed for predicting crude oil viscosity. However, these correlations are limited to predict the oil viscosity at specified conditions. In the present work, an extensive experimental data of oil viscosities collected from different samples of Iraqi oil reservoirs was applied to develop a new correlation to calculate the oil viscosity at various operating conditions either for dead, saturated or under saturated reservoir. Validity and accuracy of the new correlation was confirmed by comparing the obtained results of this correlation and other ones, with experimental data for Iraqi oil samples. It was observed that the new correlation gave the most accurate agreement with the experimental data.